PELANGGARAN HAK PEREMPUAN DI AFGHANISTAN SELAMA KEKUASAAN REZIM TALIBAN BERDASARKAN KONVENSI CEDAW - Tsabitah Rizqi Ekanoviarini; Aji Wibowo (Fakultas Hukum Universitas Trisakti, 2022)
Much debate erupted over the Taliban's return to Afghanistan, particularly in relation to women's human rights. Afghanistan becomes legally obligated by CEDAW after ratifying it, and as a result, must carry out the conditions outlined in its domestic laws and regulations. In actuality, the Taliban rule continues to violate human rights, notably by restricting the rights of women. The CEDAW Convention serves as the foundation for Afghanistan's state responsibility for violations of women's rights in Afghanistan, and this legal academic study addresses many human rights violations against women in Afghanistan under the Taliban government. Use of secondary data gathered through secondary sources has made this research, which is descriptive in character and normative in nature, the data is processed qualitatively and conclusions are drawn using deductive logic. The results of the research, discussion and conclusions of this research are that the state of Afghanistan is considered to have violated international treaties and Afghanistan as a state must be held accountable for the actions that have been carried out by its state organs.